2017
DOI: 10.1007/s11136-017-1579-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a short three-dimensional inventory of character strengths

Abstract: TICS is expected to be used for screening populations at risk, and a tool to aid mental health professionals in group-based treatment/intervention planning. It also should be noted that this short inventory should be used with caution for individual decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 68 publications
5
48
0
4
Order By: Relevance
“…The findings revealed that general self‐efficacy had a positive correlation with time management disposition, which is in agreement with the results of some previous studies (Duan & Bu, ). Considering the significant influences of self‐efficacy on time management disposition, the authors tend to think that the improvement of self‐efficacy is necessary and would contribute to the promotion of the value of time management and time availability.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The findings revealed that general self‐efficacy had a positive correlation with time management disposition, which is in agreement with the results of some previous studies (Duan & Bu, ). Considering the significant influences of self‐efficacy on time management disposition, the authors tend to think that the improvement of self‐efficacy is necessary and would contribute to the promotion of the value of time management and time availability.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the time management disposition of nursing managers in China was at a favourable level, the highest level being recorded for sense of time's value, followed by sense of time efficacy and time monitoring ability. The sense of time's value is the basis of time monitoring and sense of time efficacy (Duan & Bu, ). Only when individuals have a high sense of time's value and fully realize the importance of time for personal development, they can consciously monitor their own time and learn and master the corresponding time management skills so as to improve their work efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations